An analysis of the 2024 Romanian Presidential and parliamentary elections - Örmeci, Ozan (İstanbul Kent Üniversitesi, 2025)
The presidential and parliamentary elections held in Romania in late 2024 caused a major political crisis, with uncertainty coming to the fore due to the unexpectedly large success of the far-right candidate Călin Georgescu in the first round of the presidential elections and the lower-than-expected performance of the two mainstream political formations in the country, the Social Democratic Party (PSD) and the National Liberal Party (PNL). As if this was not enough, the cancellation and postponement of the elections by the Romanian Constitutional Court due to allegations of Russian interference in the elections increased uncertainty and democratic concerns in the country. Nevertheless, the parliamentary elections held at the end of the year were held without incident and a new government was formed democratically. In this study, the Romanian political system and the elections that were hold in 2024 will be analyzed. To do that, the author will first provide some background and statistical information about Romania for readers who are not familiar with the topic.

Romanya’da 2024 yılı sonlarında düzenlenen Cumhurbaşkanlığı ve parlamento seçimleri önemli bir siyasi krize neden olmuş; Cumhurbaşkanlığı ilk tur sonucunda aşırı sağcı aday Călin Georgescu’nun beklenmedik büyük başarısı ve ülkedeki iki ana akım siyasal oluşum olan Sosyal Demokrat Parti (PSD) ve Ulusal Liberal Parti’nin (PNL) beklentilerin altında kalması nedeniyle belirsizlik ön plana çıkmıştır. Bu yetmezmiş gibi, Romanya Anayasa Mahkemesi tarafından Rusya’nın seçime müdahil olduğu yönündeki iddialar nedeniyle seçimlerin iptal edilerek ertelenmesi ülkedeki belirsizlik ve demokratik endişeleri arttırmıştır. Buna karşın, yine yıl sonunda düzenlenen parlamento seçimleri olaysız atlatılmış ve yeni hükümet demokratik şekilde kurulabilmiştir. Bu çalışmada, Rumen siyasal sistemi ve 2024 yılı içerisinde düzenlenen seçimler analiz edilecektir. Bunu yapmak için, yazar, öncelikle konuya aşina olmayan okuyucular için Romanya hakkında bazı arka plan bilgileri ve istatistiksel veriler sunacaktır.
2024 Romanya Cumhurbaşkanlığı ve parlamento seçimlerine dair bir analiz
Keywords: Romania; Romanian political system; Marcel Ciolacu; Semi Presidency; Romanya; Rumen siyasal sistemi; Yarı Başkanlık